2019
DOI: 10.1093/ofid/ofz360.361
|View full text |Cite
|
Sign up to set email alerts
|

286. Hepatitis B Vaccine Compliance: Comparing 2-Dose and 3-Dose Vaccines

Abstract: BackgroundLess than 1 in 3 US adults who initiated the 3-dose (0, 1, 6 months) hepatitis B vaccine series have completed it. HepB-CpG (Heplisav-B; Dynavax) is a new licensed adjuvanted vaccine that requires only 2 doses (0, 1 month). As part of a cluster study performed at Kaiser Permanente Southern California, we compared compliance with second dose and series completion for HepB-CpG vs. comparator vaccine (Engerix-B; GlaxoSmithKline) recipients.MethodsThe cohort included adults not on dialysis who received t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The topic of our study is of current importance, as the occurrence of AMI in recipients of HepB‐CpG vaccine and HepB‐alum vaccine is being compared in an ongoing FDA‐mandated post‐licensure study of HepB‐CpG vaccine 7 . Safety findings from the post‐licensure study may be pivotal for influencing future recommendations for adult hepatitis B vaccination, especially among individuals with DM, given the shorter two‐dose schedule of HepB‐CpG vaccine 15 . The observed lack of association of AMI with HepB‐alum vaccine receipt in this study lends support to the use of a HepB‐alum vaccine comparator in the post‐licensure study.…”
Section: Discussionmentioning
confidence: 60%
“…The topic of our study is of current importance, as the occurrence of AMI in recipients of HepB‐CpG vaccine and HepB‐alum vaccine is being compared in an ongoing FDA‐mandated post‐licensure study of HepB‐CpG vaccine 7 . Safety findings from the post‐licensure study may be pivotal for influencing future recommendations for adult hepatitis B vaccination, especially among individuals with DM, given the shorter two‐dose schedule of HepB‐CpG vaccine 15 . The observed lack of association of AMI with HepB‐alum vaccine receipt in this study lends support to the use of a HepB‐alum vaccine comparator in the post‐licensure study.…”
Section: Discussionmentioning
confidence: 60%
“…In a recent study of 6500 HepB-CpG recipients and 7733 Engerix-B recipients, HepB-CpG recipients were 5 times more likely to complete the vaccine series compared with Engerix-B recipients (adjusted hazard ratio = 5.17; 95% CI = 3.84-6.98). 30 These findings suggest that the 2-dose series results in greater adherence to vaccine series completion compared with the traditional 3-dose HBV series, potentially contributing to the reduction in the public health burden of this vaccine-preventable disease.…”
Section: Relevance To Patient Care and Clinical Practicementioning
confidence: 87%
“…A prior meta‐analysis showed that financial incentives, followed by accelerated vaccine schedules had the highest efficacy in helping the PWID to complete the scheduled 3‐dose vaccination series 57 . The newly available and equally efficacious Heplisav‐B vaccine which requires only two doses over only 1 month (vs 3 doses over 6 months) should be considered in this population to improve compliance and adherence 58 …”
Section: Gaps In Hbv Vaccination and Preventionmentioning
confidence: 99%